2020
DOI: 10.1007/s11748-020-01351-0
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in non-small cell lung cancer patients who underwent surgery after induction therapy

Abstract: Objectives Lung cancer patients have been reported to have a high incidence of venous thromboembolism (VTE) and a high recurrence rate of VTE. However, there are no detailed reports of VTE in lung cancer patients who underwent surgery after induction therapy. We examined the incidence and clinical features of VTE in these patients. Methods We retrospectively evaluated 89 patients with non-small cell lung cancer who underwent surgery after induction therapy at our department between April 2009 and March 2018. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Postoperative VTE is not uncommon in patients with lung cancer who undergo surgery. Previous studies reported that the incidence of VTE after lung cancer surgery ranges from 4.5% to 13.9% 10 12 22 37–40. For patients with lung cancer who undergo thoracic surgery, there are some specific risk factors for postoperative VTE development.…”
Section: Assessmentmentioning
confidence: 99%
“…Postoperative VTE is not uncommon in patients with lung cancer who undergo surgery. Previous studies reported that the incidence of VTE after lung cancer surgery ranges from 4.5% to 13.9% 10 12 22 37–40. For patients with lung cancer who undergo thoracic surgery, there are some specific risk factors for postoperative VTE development.…”
Section: Assessmentmentioning
confidence: 99%
“…M e t h o d s t o p r e v e n t V T E i n c l u d e m e c h a n i c a l prophylaxis, which usually uses intermittent pneumatic compression (IPC) and medical elastic stockings (MES), and pharmacological prophylaxis such as low-molecular-weight heparin (LMWH). In Western countries, both mechanical and pharmacological prophylaxis are widely used as standard preventive methods for VTE after routine surgery (9)(10)(11). Widespread overuse of LMWH is likely to translate into a risk of adverse events, including bleeding events.…”
Section: Introductionmentioning
confidence: 99%